A Scoping Review on Use of Drugs Targeting the JAK/STAT Pathway in Psoriasis - Gómez-García, Francisco; Gómez-Arias, Pedro Jesús; Montilla-López, Ana; Hernández-Parada, Jorge; Sanz-Cabanillas, Juan Luís; Ruano, Juan; Parra-Peralbo, Esmeralda (Frontiers in Medicine, 2022)
The Janus kinase/Signal transducer and activator of transcription (JAK/STAT) pathway is known to be involved in inflammatory immune-mediated skin diseases, including psoriasis. The development of drugs targeting the JAK/STAT signaling pathway presents new treatment opportunities for psoriasis. However, the application of JAK inhibitors for the treatment of dermatological disorders is still in its early stages of development. The evidence found on the efficacy and safety of drugs targeting the JAK/STAT pathway in patients with psoriasis comes from 118 articles reporting the results of 34 randomized clinical trials (RCTs). Nine different drugs administered through various routes were identified (systemic: peficitinib, baricitinic, solcitinib, itacitinib, abrocitinib, deucravacitinib, and brepocitinib; topical: ruxolitinib; and both: tofacitinib). Only tofacitinib and deucravacitinib have undergone phase III clinical trials, being the only ones tested with active comparators etanercept and apremilast, respectively. Proportions of Psoriasis Area and Severity Index (PASI) and Physician's Global Assessment (PGA) were the efficacy variables most frequently studied in systemic treatments. Only two RCTs declared the safety data collected by systematic assessment; the only systemic drug with phase III data was tofacitinib. Tofacitinib 5 mg twice daily (BID)/10 mg BID efficacy was compared with etanercept 50 mg/week and a placebo. At 12–16 weeks PASI 75/PGA 01 ranges were: 38.07–80 %/37.16–67.4 % for tofacitinib 5 mg BID; 54.79–100 %/50–75.6 % for tofacitinib 10 mg BID; 58.8 %/66.8 % for etanercept, date from one only study; and 0–33.3 %/9.04–33.3 % for the placebo group. Other drugs in earlier stages of development showed values within these ranges. The most frequent adverse events (AE) were nasopharyngitis and upper respiratory tract infections in all treatment groups. The trials conducted to date have been financed directly or indirectly by the pharmaceutical industry, which must be taken into account when interpreting the results of the trials. Psoriasis treatment is currently symptomatic and could potentially present a significant risk of toxicity. Therefore, the design of principal efficacy outcome measures considering the impact of the outcome on quality of life and a drug assessment methodology aimed at improving safety would probably strengthen the evidence and decision-making process.